PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA YANG DIMEDIASI OLEH KETERLIBATAN KERJA - Assegaf, Doni Akbar; Wajdi, M. Farid (Prosiding University Research Colloquium, 2022)
urrently there are many challenges faced along with developments and dynamics in the business environment. One of these challenges is how the human resources owned by the organization can be further developed because employees are a valuable resource. They have a significant contribution to achieving organizational success in the future. Human resources are an element of organizational resources that are realized through solid abilities from the physical strength of the individual, behavior, and the nature of a person who is influenced by the environment and heredity, while the results of the work provided by each individual come from demands to fulfill motives or needs to be satisfied and according to expectations. The purpose of this study, namely: To analyze the influence of organizational culture on job satisfaction. To analyze the effect of organizational culture on work engagement. To analyze the effect of job involvement on job satisfaction. To analyze whether job involvement mediates the relationship between organizational culture and job satisfaction. This type of research used in research is a quantitative method. The population in this study are employees of CV. Putera Tunggal Gemilang. The sampling technique in this study is non-probability sampling. The sampling technique used is purposive sampling. The number of samples in this study were 100 respondents. The data analysis technique in this study uses Partial Least Square (PLS) with the help of SmartPLS software. PLS-SEM analysis includes two models, namely the outer model l and the inner model. The results of the analysis show that organizational culture has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on work involvement, work involvement has a positive and significant effect on job satisfaction, and work involvement partially mediates the influence of organizational culture on job satisfaction.